KAJIAN AWAL UNTUK MEMPERCEPAT PEMULIHAN KONDISI SOSOAL EKONOMI MASYARAKAT TERKENA BENCANA ERUPSI GUNUNG MERAPI MELALUI BUDIDAYA ULAT SUTERA - Robertus Sudaryanto; Supriyadi Supriyadi; Purwanto Purwanto (Faculty of Agriculture, Universitas Sebelas Maret, 2011)
Title : Initial Assessment to Accelerate Recovery of The Affected Community Social Economic Mount Merapi Eruption Through The Cultivation of Silkworms. Research purposes to obtain the suitability of land for mulberry (Morus sp) in the affected area 2010 eruption of Mount Merapi, in Balerante Kemalang Klaten in Central Java. This information is necessary to create activities that can accelerate the recovery of socio‐economic conditions of society through silkworm farming. The method used is an inventory of soil and land characteristics through field surveys. Step (1) an inventory of climatic factors, soil and topography to make the Land Unit Map (SPT). Stage (2) analysis of soil fertility in the laboratory to complement the characteristics of land that has not been obtained at the time of field survey. Stage (3) develop / describe the characteristics of the land on each Land Unit on our soil. Stage (4) The process of evaluating the suitability of the land, the match (matching) characteristics of land with mulberry plant growth requirements. The results of our actual and potential land suitability. This map is useful to provide guidance on the cultivation of mulberry plants. (Morus sp.), Results showed that most of land unit in this area has a fitness class S2nr (Quite in accordance with the limiting nutrient retention)Keywords: actual and potential land suitability, land characteristics, referrals, and cultivation